المؤثرات العقلية وطرق معالجتها في السنة النبوية: قراءة في الأساليب والآليات - بن عمراوي، الياسين Bin Amrawi, Alyasin (جامعة الأمير عبدالقادر للعلوم الإسلامية - كلية الآداب والحضارة الإسلامية, 2023)
يتناول البحث قضية مهمة من قضايا المجتمع وآفة خطيرة من آفاته، وهي تعاطي المسكرات والمؤثرات العقلية، وسعيا لبحث مسالك وأساليب السنة النبوية في محاربتها والقضاء عليها، والتقليل من أثارها السيئة على النفس والمجتمع بإهلاكه بأمراض عقلية عويصة تؤثر على مبادئ وقيم المجتمعات المحافظة، يتم رصد أهم النصوص النبوية والأثار وتحليلها ومناقشتها، بغية شرح آليات حفظ العقل، إذ كيف يمكن للسنة النبوية أن تكون رافدا من روافد محاربة المؤثرات العقلية؟ وكيف نستثمرها في المجتمعات المغاربية وفي المجتمع الجزائري خاصة؟، وبناء على هذا توصل إلى نتائج مهمة تتعلق بوجوب مخاطبة هذه الأمة بدينها لإصلاحها، وضرورة الاستعانة بالطرق المبثوثة في السنة النبوية في حل المشاكل ومحاربة الآفات الاجتماعية خاصة المسكرات والمخدرات، وأهمية نصب لجان وطنية شرعية وإعلامية ومجتمعية للسعي إلى الأخذ بأيدي المدمنين إلى الصلاح والإصلاح، بحلول واقعية بناء على وازع ديني وآليات اقتصادية فعالة. The research addresses an important issue within society, namely the problem of substance abuse and mental influences. It aims to explore the methods and approaches found in the Prophetic Sunnah and tradition for combating and eliminating these issues, as well as minimizing their effects on individuals and society. The destructive consequences of substance abuse, including severe mental illnesses that impact the principles and values of conservative communities, are examined. The study focuses on identifying significant Prophetic texts and analyzing them in order to understand the mechanisms of preserving mental well-being. It investigates how the Prophetic tradition can serve as a source for combating mental influences and how it can be applied within Maghreb societies, particularly in the Algerian society. Based on this analysis, important findings emerge regarding the necessity of addressing the religious principles of the community for its reformation, as well as the importance of utilizing the established methods in the Prophetic teaching sunnah to solve problems and combat social issues, specifically substance and drugs abuse. The establishment of legitimate, informative, and societal committees is emphasized to guide addicts towards reform and rehabilitation, using realistic approaches grounded in religious principles and effective economic mechanisms.
Keywords: الأحاديث النبوية -- المقاصد الشرعية -- الآفات الاجتماعية -- المغيبات العقلية -- إدمان المخدرات